Antidiabetic agent use and clinical outcomes in patients with diabetes hospitalized for COVID-19: a systematic review and meta-analysis - Jordan N. Keels; Isabella R. McDonald; Christopher S. Lee; Andrew A. Dwyer; Andrew A. Dwyer (Frontiers in Endocrinology)
BackgroundThe effect of antidiabetic agents on mortality outcomes is unclear for individuals with diabetes mellitus (DM) who are hospitalized for COVID-19.PurposeTo examine the relationship between antidiabetic agent use and clinical outcomes in individuals with DM hospitalized for COVID-19.MethodsA systematic review of the literature (2020-2024) was performed across five databases. Included articles reported primary research (English) reporting clinical outcomes of adult patients (≥18 yrs.) with DM receiving antidiabetic agents who were hospitalized for COVID-19. Following PRISMA guidelines articles underwent independent dual review. Quality appraisal was completed for included studies. Independent reviewers used a structured data extraction form to retrieve relevant data. Aggregated data were synthesized by treatment regimen and reported descriptively. Random effects meta-analyses were performed to assess relative risk and prevalence of mortality.ResultsAfter removing duplicates, title and abstract screening of 4,898 articles identified 118 articles for full-text review and 35 articles were retained for analysis. Included articles were primarily from China (15/35, 43%) and retrospective in nature (31/35, 89%). Fourteen studies (40%) assessed multiple antidiabetic agents, fifteen studies (42%) focused on metformin, three studies (9%) assessed the use of DPP-4 inhibitors, and three single studies (9%) investigated the use of insulin, TZD, and SGLT2 inhibitors. Despite differences among studies, the overall relative risk of mortality among metformin and DPP-4 inhibitor users was 0.432 (95% CI = 0.268-0.695, z = 3.45, p < 0.001) and the overall prevalence of mortality among all antidiabetic users was 16% (95% CI = 13%–19%, z = 10.70, p < 0.001).Conclusions and implicationsSynthesis of findings suggest that patients who remained on oral agents (with/without supplemental insulin therapy) exhibited decreased mortality and lower inflammatory markers. Results indicate that individuals with DM should continue oral antidiabetic agents with additional basal insulin as needed to improve glycemic control and reduce mortality. Further work is needed to uncover mechanism(s) and clarify medical management approaches.